2004
DOI: 10.2172/826908
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Gravity and Inflation

Abstract: Using the Ashtekar-Sen variables of loop quantum gravity, a new class of exact solutions to the equations of quantum cosmology is found for gravity coupled to a scalar field that corresponds to inflating universes. The scalar field, which has an arbitrary potential, is treated as a time variable, reducing the hamiltonian constraint to a time-dependent Schroedinger equation. When reduced to the homogeneous and isotropic case, this is solved exactly by a set of solutions that extend the Kodama state, taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…case [31]. It was also found that a truncation to homogeneous cosmology can be made normalizable by making the cosmological constant depend on a physical field and making wavepackets in that field's value [32]. Another approach to the issue is in [33].…”
Section: An Explicit Examplementioning
confidence: 99%
“…case [31]. It was also found that a truncation to homogeneous cosmology can be made normalizable by making the cosmological constant depend on a physical field and making wavepackets in that field's value [32]. Another approach to the issue is in [33].…”
Section: An Explicit Examplementioning
confidence: 99%
“…Another approach to inflation within loop quantum gravity is given in [119]. Exact homogeneous quantum states can be constructed for general relativity coupled to a scalar field with an arbitrary potential.…”
mentioning
confidence: 99%